Greek writing from Knossos to Homer : a linguistic interpretation of the origin of the Greek alphabet and the continuity of ancient Greek literacy - Woodard, Roger D. (OUP E-Books., 1997)
Greek Writing from Knossos to Homer examines the origin of the Greek alphabet. Departing from previous accounts, Roger Woodard places the advent of the alphabet within an unbroken continuum of Greek literacy beginning in the Mycenaean era. He argues that the creators of the Greek alphabet, who adapted the Phoenician consonantal script, were scribes accustomed to writing Greek with the syllabic script of Cyprus.